Economic Valuation of Tourism Attraction of Jatijajar Cave in Kebumen Regency - Susilowati, Indah; Syah, Angga Ferdinan; Suharno, Suharno; Aminata, Jaka (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
The research aims at estimating the level of Willingness to Pay of the tourists for the Tourism Attraction of Jatijajar Cave in Kebumen Regency. The primary data is obtained from 105 respondents by using the Multistage Sampling and five key persons by using the Purposive Sampling. The characteristics of respondents show that some of the tourists are male, around 21 to 30 years old. The result of Contingent Valuation Methods shows that the WTP of the tourists of Jatijajar Cave has the average about Rp 17,000.00 and the total value of WTP is about Rp 5,231,410,000.00. The novelty in this research is using Contingent Valuation Methods approach to educate the visitors through the hypothetical-market that has been built by two scenarios of willingness to pay for the visitors at Jatijajar Cave tourism attraction as a compensation for the development of tourism attraction.